2017
DOI: 10.2319/062017-407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bone regeneration materials and tooth movement timing on canine experimental orthodontic treatment

Abstract: The Bio-Oss group had favorable radiologic features (higher alveolar bone level and bone density with less premolar tipping) but showed slower OTM than the control group. The late OTM subgroup had favorable radiologic features and showed faster tooth movement than the early OTM in the β -TCP group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 14 publications
1
45
0
Order By: Relevance
“…In this study, similar OTM distance and rate of OTM were observed in control, DBB, and BioCaP group, indicating that both DBB and BioCaP did not obstruct the OTM during 8 weeks. But Machibya et al (2018) reported higher OTM in the DBB group compared to CaP or no graft group. This discrepancy might be caused by the different starting times of orthodontic traction, i.e., at least 1 month after grafting and OTM timing of 6 weeks (Machibya et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, similar OTM distance and rate of OTM were observed in control, DBB, and BioCaP group, indicating that both DBB and BioCaP did not obstruct the OTM during 8 weeks. But Machibya et al (2018) reported higher OTM in the DBB group compared to CaP or no graft group. This discrepancy might be caused by the different starting times of orthodontic traction, i.e., at least 1 month after grafting and OTM timing of 6 weeks (Machibya et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
“…But Machibya et al (2018) reported higher OTM in the DBB group compared to CaP or no graft group. This discrepancy might be caused by the different starting times of orthodontic traction, i.e., at least 1 month after grafting and OTM timing of 6 weeks (Machibya et al, 2018). Our results indicate that early orthodontic traction (1 week after grafting) in BioCaP grafted defect enhanced alveolar bone defect healing without hampering OTM.…”
Section: Discussionmentioning
confidence: 85%
“…It should be noted that the method of analysis is crucial to the validity of the conclusion, since results of bone morphometry depend on the VOI. Previous studies selected VOIs either in function of the pressure/tension sides [16] or anatomic sites such as at the furcation [50,51] or mesial root [15] [52] of the rst molar, in different jaws and animal species [53,54] . However, these areas are di cult to be determined accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar bone metabolism is closely related to the speed of orthodontic tooth movement, which results in different bone turnover rates under orthodontic forces based on patient-speci c traits 13,14 . In an experimental study of beagle dogs, the group whose bone density was increased by promoting bone formation exhibited signi cantly reduced tooth movement speed compared to the control group, indicating that the quality of alveolar bone affected orthodontic treatment duration 15 . These individual differences in physiological characteristics stem from respective genetic differences attributed to gene polymorphisms, wherein gene expression levels vary between individuals.…”
Section: Introductionmentioning
confidence: 99%